Preventive effect of jicama (Pachyrhizus erosus) fiber against diabetes development in mice fed with high-fat diet - Putra Santoso, Rita Maliza, Siti Jamalul Insani, Qonitah Fadhila, Resti Rahayu (Journal of Applied Pharmaceutical Science, 2021)
The health benefits of dietary fiber have been extensively explored; however, studies focusing on edible fibers extracted from tuberous plants remain limited. This study aimed to investigate whether the supplementation of dietary fiber extracted from jicama (Pachyrhizus erosus, Fabaceae) tuber is capable of preventing the development of type 2 diabetes mellitus (T2DM) induced by high-fat diet (HFD). We carried out an experimental study using adult male mice fed with four different diets including normal diet, HFD, and HFD supplemented with 10% and 25% of jicama fiber (n = 10 in each group) for 8 weeks. Furthermore, random blood glucose, fasting blood glucose, and glucose tolerance were measured and the histopathological alterations of the pancreas were examined. We revealed that the jicama fiber at the dose of 10% and 25% effectively precluded a marked increase in random and fasting blood glucose levels and sustained the glucose tolerance of HFD-fed mice. Moreover, jicama fiber was also effective in preventing the development of hypertrophy and hyperplasia of the islet of Langerhans as well as ectopic fat deposition and fibrosis in the pancreas. Therefore, the supplementation of jicama fiber effectively prevented T2DM development including dysregulated blood glucose and histopathological alterations of the pancreas caused by HFD consumption.
Keywords: Obesity, type 2 diabetes mellitus, metabolic diseases, fibrosis, glucose tolerance.